Exit Dynamics with Adjustment Costs - Rolf Golombek; Arvid Raknerud (Statistics Norway, Research Department, 2005)
We use the Stock and Wise approximation of stochastic dynamic programming in order to identify the extent to which profitability can explain exit behavior. In our econometric model, heterogeneous firms engage in Bertrand (price) competition. Firms produce heterogeneous products, using labor, materials and capital as inputs. The stock of capital is changed through investments and disinvestments, where the firm incurs adjustment costs due to partial irreversibilities. The model is estimated for six manufacturing industries using Norwegian micro data for the period 1993-2002. We find that increased profitability lowers the exit probability, and this effect is statistically significant in all industries, while, ceteris paribus, high adjustment costs significantly decrease the probability of exit in five of the industries. Exiting firms are characterized by persistently, although only moderately higher, annual exit probabilities than the average firm. There is no tendency for exiting firms to have a high probability of exit just prior to exit.
Keywords: C33; C51; C61; C72; D21; 330; Firm exit; adjustment costs; Bertrand game; manufacturing firms; mixed logit; state space model.